MRI study of atherosclerotic plaque progression using ultrasmall superparamagnetic iron oxide in Watanabe heritable hyperlipidemic rabbits - Kaneko, C (Br J Radiol, 2015)
OBJECTIVE: The purpose of this study was to evaluate plaque progression by using MRI with ultrasmall superparamagnetic iron oxide (USPIO) and by histopathological studies. METHODS: We divided 12 Watanabe heritable hyperlipidemic (WHHL) rabbits into 4 groups based on their age (3, 9, 14 and 26 months) and injected them intravenously with 0.8 mmol (Fe) kg(−1) of USPIO (size, 32 nm; concentration, 15 mg dl(−1)). On the fifth post-injection day, they were again given an intravenous injection with 40 μmol kg(−1) of the same USPIO, and MR angiography (MRA) was performed. The signal-to-noise ratio (SNR) in regions of interest in the wall of the upper abdominal aorta was calculated on coronal images. Specimens from the same level of the aorta were subjected to iron staining and RAM-11 immunostaining and used for histopathological study. For statistical analysis of the MRA and histopathological findings, we used analysis of variance [Tukey's honest significant difference (HSD) test]. RESULTS: In 9-month-old rabbits, the SNR was significantly lower than in rabbits of the other ages (p < 0.01), and the area of RAM-11 (DAKO Corporation, Glostrup, Denmark) and iron uptake in the aortic wall was significantly larger (RAM-11, p < 0.01; iron, p < 0.05). These areas were the smallest in 3-month-old rabbits. CONCLUSION: Histopathologically, the number of macrophages was the greatest in 9-month-old rabbits. Our findings indicate that the SNR on MRI scans reflects the number of macrophages in the aortic wall of WHHL rabbits. ADVANCES IN KNOWLEDGE: USPIO-enhanced MRI visualized the accumulation of macrophages in early atherosclerotic plaques of WHHL rabbits in the course of natural progression.